1989
DOI: 10.1029/gb003i004p00375
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide flux from dry tropical forests

Abstract: Fluxes of nitrous oxide were determined in several sites in drought‐deciduous tropical forest, an extensive but little‐studied biome. N2O‐N fluxes from eight sites within intact Mexican forest averaged 0.91 ng cm−2 h−1 during the wet season; they were virtually absent in the dry season. Two subsistence maize fields yielded increased soil N2O‐N fluxes, while five pastures were more variable. Watering during the dry season caused a substantial but short‐lived pulse of N2O. Similar fluxes were observed in less‐in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 17 publications
1
11
1
1
Order By: Relevance
“…At the PF and SF site, the coefficients of variation (c v ) for N 2 O emissions of the entire measurement period (daily aggregated and analysed for any single chamber) ranged from 35% to 62% (Table 2). The observed variations in N 2 O emissions this study are within the c v -range of 14-125% reported for tropical rainforests soils in Queensland, Australia (Breuer et al 2000;Kiese and Butterbach-Bahl 2002;Butterbach-Bahl et al 2004b), but lower than the range of 94-195% reported for tropical rain forest soils in Amazonia (Vitousek et al 1989;Verchot et al 1999). Despite the fact that the rubber plantation was fertilised with approximately 55 kg N ha -1 yr -1 , weighted mean N 2 O emission fluxes of the RP site were significantly lower than those observed at the nearby SF site or at the PF site.…”
Section: Discussioncontrasting
confidence: 38%
“…At the PF and SF site, the coefficients of variation (c v ) for N 2 O emissions of the entire measurement period (daily aggregated and analysed for any single chamber) ranged from 35% to 62% (Table 2). The observed variations in N 2 O emissions this study are within the c v -range of 14-125% reported for tropical rainforests soils in Queensland, Australia (Breuer et al 2000;Kiese and Butterbach-Bahl 2002;Butterbach-Bahl et al 2004b), but lower than the range of 94-195% reported for tropical rain forest soils in Amazonia (Vitousek et al 1989;Verchot et al 1999). Despite the fact that the rubber plantation was fertilised with approximately 55 kg N ha -1 yr -1 , weighted mean N 2 O emission fluxes of the RP site were significantly lower than those observed at the nearby SF site or at the PF site.…”
Section: Discussioncontrasting
confidence: 38%
“…This huge dataset allowed us (1) to identify short‐term changes in the magnitude of N 2 O emissions, (2) to demonstrate seasonal variability of N 2 O emissions with a hitherto unknown time resolution and (3) to calculate precise annual loss rates of N 2 O from our site. The short‐term variability of N 2 O emissions from tropical rain forest soils and its dependency on rainfall events have already been highlighted by Breuer et al [2000] and Kiese and Butterbach‐Bahl [2002] for different rain forest sites in Australia and by Vitousek et al [1989] during a rewetting experiment of a tropical forest soil in Chamela, Mexico. Our observations show, that it is essential to have continuous measurements of N 2 O emissions, at least during wet season conditions, to reliably estimate annual loss rates.…”
Section: Discussionmentioning
confidence: 90%
“…Castaldi et al (2004) analyzing published N 2 O fluxes from tropical seasonally dry ecosystems, concluded that N 2 O fluxes were strongly limited by soil characteristics and that only in fertile soils with medium texture the conversion of land could induce significant variations of N 2 O fluxes respect to the control sites. Other studies have not shown any effect of clearing and conversion of savanna into pastures; in some cases, a reduction of N 2 O fluxes in the pasture ecosystems in the years following land conversion has been observed (Vitousek et al , 1989; Erickson & Keller, 1997; Verchot et al , 1999; Melillo et al , 2001).…”
Section: Resultsmentioning
confidence: 96%